Proactive Monitoring of Chronic Conditions Using WMDs in Primary Care: Protocol of a Multicenter Feasibility Randomized Controlled Trial Across Italy and Finland - Elisabetta Mezzalira; Luisa Saiani; Anna Axelin (Dissertation Nursing)
BACKGROUND: Wearable monitoring devices (WMDs) have emerged as a promising tool for supporting self-management of chronic conditions, but sustained long-term use remains a challenge. This multicentre feasibility randomized controlled trial aims to develop and evaluate a proactive monitoring intervention utilizing WMDs for individuals with chronic conditions in primary care settings across Italy and Finland.